Was an increase in cocaine use among injecting drug users in New South Wales, Australia, accompanied by an increase in violent crime? - Conroy Elizabeth; Hall Wayne; Day Carolyn; Degenhardt Louisa; Gilmour Stuart (BMC, 2005)
Abstract Background A sharp reduction in heroin supply in Australia in 2001 was followed by a large but transient increase in cocaine use among injecting drug users (IDU) in Sydney. This paper assesses whether the increase in cocaine use among IDU was accompanied by increased rates of violent crime as occurred in the United States in the 1980s. Specifically, the paper aims to examine the impact of increased cocaine use among Sydney IDU upon police incidents of robbery with a weapon, assault and homicide. Methods Data on cocaine use among IDU was obtained from the Illicit Drug Reporting System (IDRS). Monthly NSW Police incident data on arrests for cocaine possession/use, robbery offences, homicides, and assaults, were obtained from the Bureau of Crime Statistics and Research. Time series analysis was conducted on the police data series where possible. Semi-structured interviews were conducted with representatives from law enforcement and health agencies about the impacts of cocaine use on crime and policing. Results There was a significant increase in cocaine use and cocaine possession offences in the months immediately following the reduction in heroin supply. There was also a significant increase in incidents of robbery where weapons were involved. There were no increases in offences involving firearms, homicides or reported assaults. Conclusion The increased use of cocaine among injecting drug users following the heroin shortage led to increases in violent crime. Other States and territories that also experienced a heroin shortage but did not show any increases in cocaine use did not report any increase in violent crimes. The violent crimes committed did not involve guns, most likely because of its stringent gun laws, in contrast to the experience of American cities that have experienced high rates of cocaine use and violent crime.